Some new traveling wave solutions of the nonlinear reaction diffusion equation by using the improved (G′/G)-expansion method - Naher, Hasibun; Abdullah, Farah Aini (© 2012 Mathematical Problems in Engineering, 2016)
This article was published in the Mathematical Problems in Engineering [© 2012 Hasibun Naher and Farah Aini Abdullah.] and the definite version is available at : http://dx.doi.org/10.1155/2012/871724 The Journal's website is at:https://www.hindawi.com/journals/mpe/2012/871724/